Impact of enjoyment on the usage continuance intention of video-on-demand services - Pereira, Rita (2021)
Pereira, R., & Tam, C. (2021). Impact of enjoyment on the usage continuance intention of video-on-demand services. Information and Management, 58(7), 1-11. [103501]. https://doi.org/10.1016/j.im.2021.103501